Changes in Hail Damage Potential in Major Australian Cities With Global Warming - Timothy H. Raupach; Joanna Aldridge (Geophysical Research Letters)
Abstract In Australia, hailstorms cause large insured losses, with damage exacerbated by larger hailstones or accompanying strong winds. Changes to the frequency and severity of such storms under global warming are not well understood. We used downscaled simulations over major cities and a remote region in Australia, covering 65% of the Australian population, to estimate storm‐season hail frequency, hailstone size, and hail‐proximal wind speeds for historical and future epochs separated by a ∼2.4◦C increase in mean global temperature. Extreme value analysis was used to examine changes in daily maximum hail sizes and hail‐proximal winds. The projections show increases in hail frequency in the Sydney/Canberra and Brisbane regions and robust increases in maximum hail size around Melbourne, Sydney/Canberra, Kalgoorlie, and Perth. Damaging (≥90 km h−1) hail‐proximal winds are projected to decrease in Melbourne, Sydney/Canberra and Perth, although daily mean hail‐proximal wind speeds are projected to increase in Sydney/Canberra and Perth.